Unmet needs and opportunities for improving care for patients with advanced lung cancer on targeted therapies: a qualitative study. Issue 3 (23rd March 2020) - Al Achkar, Morhaf; Marchand, Lucille; Thompson, Matthew; Chow, Laura Q M; Revere, Debra; Baldwin, Laura-Mae
Abstract : Objective: Lung cancer is increasingly recognised as a heterogeneous disease. Recent advances with targeted therapies for lung cancer with oncogenic mutations have greatly improved the prognosis for this subset of patients, yet little is known about their experiences. This study aimed to identify the needs and explore the healthcare experiences of these advanced patients with oncogenic mutation driven lung cancer. Design: Qualitative interviews with patients with advanced or metastatic non-small cell lung cancer with oncogenic alterations in anaplastic lymphoma kinase, epidermal growth factor receptor or c-ros oncogene 1. Settings: Patients were recruited from online lung cancer support groups within the USA. Interviews were conducted remotely or in person, transcribed verbatim and analysed using an iterative inductive and deductive process. Participants: We included 39 patients (11 males and 28 females) with a median age of 48. Results: Two primary theme categories emerged: patients' unmet needs and improving healthcare experiences. Unmet needs are related to patients' desire to view their disease as a chronic illness, aspire to live a meaningful existence without financial devastation, desire for understanding along with emotional support and needing help with practical matters. Improving healthcare experiences involved patients' desire to trust the expertise of clinical providers, receive reliable care and be treated holistically and as informed partners. Conclusions: Patients with lung cancer with oncogenic mutations live uncharted experiences. Targeted therapy brings hope, but uncertainty is daunting. Patients grapple with the meaning and purpose of their lives while day-to-day obligations remain challenging. Healthcare teams are instrumental in their care experiences, and patients desire providers who are up-to-date on advances in the field and treat them as whole persons.